Pisa Syndrome in Parkinson's Disease Is Associated With Specific Cognitive Alterations - Artusi, Carlo Alberto; Montanaro, Elisa; Tuttobene, Sara; Romagnolo, Alberto; Zibetti, Maurizio; Lopiano, Leonardo (Frontiers in Neurology, 2019)
BACKGRUOND Pisa syndrome (PS) is a lateral flexion of the trunk frequently associated with Parkinson’s disease (PD). The pathophysiology of PS remains unclear, but the role of cognitive deficits has been postulated. METHODS We included 12 consecutive PD patients with PS (PS+) and 12 PD patients without PS (PS-) matched for gender, age, level of education, PD duration, and PD stage. As primary aim, we compared the neuropsychological scores of 16 tests evaluating 6 cognitive domains between PS+ and PS-. Additionally, we evaluated the presence of misperception of the trunk position in PS+, defined as a mismatch between the objective vs. subjective evaluation of the trunk bending angle > 5°, and analyzed whether a correlation exists between the misperception of the trunk position and alterations in the visual-spatial abilities. RESULTS PS+ group showed significantly worse performances in the visual-spatial abilities (p: 0.008), attentional domain (p: 0.001), and language domain (p: 0.023). No differences were found in the other cognitive domains nor in the general cognitive assessment. All PS+ patients showed a misperception of the trunk position, with an average underestimation of the trunk bending angle of 11.7° ± 4.3. The degree of misperception of the trunk position showed a trend towards a correlation with the visual-spatial scores (p: 0.089). CONCLUSIONS The study reveals an association between PS and specific cognitive alterations, suggesting a possible link between the abnormal posture of PD patients with PS and their cognitive functions.